História dos desastres socioambientais hidrológicos em Chapecó/SC (1911-1983) - Zenaro, Marizete Gasparin (2026)
This thesis investigates the history of socio-environmental hydrological disasters in Chapecó/SC, Santa Catarina, during the 20th century, identifying the conditions that led to the occurrence of these disasters in the municipality. The time frame of approximately seventy-five years begins with the 1911 flood that affected the riverside population along the Uruguay river and ends with the 1983 catastrophe, marked by two successive hydrological events within a sixty-day interval, with severe impacts on rural and urban areas. During this period, the municipality underwent dynamic processes of socio-spatial transformation, characterized by political and administrative emancipation, intensification of human occupation, and the consolidation of a new economic matrix that replaced the extractive base with industrialization and commercial development. These transformations altered demographic growth and the urbanization process, reconfiguring local spaces and landscapes. This thesis focuses on the socio-environmental relationship in urban and rural contexts, analyzing the reciprocal influence between extreme climatic events and human activity. The study narrates the history of disasters in the context of local human occupation, the economic losses, the material, human and environmental damage, as well as the impacts on housing and human mobility. It discusses public policies for prevention, emergency and recovery, agricultural policies of the 1970s, and current environmental legislation. It adopts the perspective of Environmental History, with the collection of data and interpretation of documentary sources, including the Report of the President of the Province of Paraná, a Message addressed to the Legislative Congress of Paraná, the Master Plan of the city of Chapecó/SC, the Meteorological Bulletin of Rio Grande do Sul, photographs, rainfall data collected by Epagri showing precipitation volumes, population data from IBGE, laws and decrees that organize land use and occupation, as well as records from the local, regional and state newspaper. The sources engage in dialogue with existing literature on the subject. It is concluded that the transformations in environmental dynamics, resulting from human occupation and urban expansion in the vicinity of the rivers of Chapecó during the 20th century, interfered with the frequency and intensity of socio-environmental hydrological disasters, increasing vulnerability and consequently economic and social damages. The newspaper, in recording such events and enabling their historical reconstruction, defined the concepts of floods, inundations, and flooding based on the context of the disasters. Public policies and current environmental legislation have proven insufficient in organizing land use and occupation and in reducing socio-environmental impact, both in urban and rural areas.